The role of local knowledge in adaptation to climate change. (20th December 2012) - Naess, Lars Otto
Abstract: Evidence from recent research suggests that local knowledge may contribute to adaptation to climate change in a number of ways. At the same time, there are concerns over its relevance for future adaptation amidst other challenges. This article aims to shed light on some of the key potentials and challenges for the application of local knowledge for adaptation, drawing on recent studies as well as findings from semi‐arid Tanzania. This article illustrates how the role of local knowledge at the local level is determined by interaction between informal and formal institutions at the local level. It suggests that assessments of the role of local knowledge for adaptation need to give more consideration to local power relations and the interaction with government strategies, while also addressing structural constraints to the use of local knowledge across scales. WIREs Clim Change 2013, 4:99–106. doi: 10.1002/wcc.204 This article is categorized under: Vulnerability and Adaptation to Climate Change > Institutions for Adaptation